Assisting the Digital Promotion through Marketplaces for MSME Entrepreneurs at Traji Village - Tusyanah Tusyanah; Fransisca Rahcmawati Indira; Jarot Tri Bowo Santoso; Edy Suryanto (STKIP Singkawang, 2022)
Traji Village, Parakan, has several superior products (Coffee, Tobacco, Traditional Snacks) produced by MSMEs but are not widely known because they have not used Shopee. This assistance activity is in the form of training and assistance for e-commerce adoption in the form of Shopee. These skills are expected to make it easier for MSME actors to carry out digital promotions. The objectives of this assistance are 1) improving knowledge of creating and managing Shopee Seller accounts and 2) improving the skills of creating and managing Shopee Seller accounts. This assistance focuses on 1) understanding and practice of creating accounts on Shopee; 2) understanding and managing products on Shopee. The method used is lecture and direct practice. The participants are 25 MSME actors in Traji Village (Producers of Coffee Powder, Cassava Chips, and Herbal Drinks). The assistance results show that 1) participants have gained knowledge in creating and managing Seller Shopee accounts, and 2) participants have skills in creating and managing Seller Shopee accounts